2022
DOI: 10.1590/1519-6984.266573
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective potential of lignan-rich fraction of Piper cubeba L. by improving antioxidant capacity in the rat's brain

Abstract: Piper cubeba contains various types of lignans. These compounds have been found to have potential pharmacological activities, one being a neuroprotector through an antioxidant mechanism, especially in the brain. This study examined the antioxidant activity of the lignan-rich fraction of P. cubeba (LF) in rat brains. The rats were given LF (200 and 400 mg/kg), Vitamin C (200 mg/kg), and a carrier as the control group for one-week p.o. The following day, rat brains were collected for antioxidant tests, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Increased oxidative stress is responsible for neuronal damage in the frontal cortex and hippocampus ( MacPherson et al, 2005 ), which is likely to impair learning. Vitamin C has an antioxidant potential that helps to oppose neurodegeneration in several ailments by conserving the antioxidant mechanism in the brain, imparting neuroprotection ( Dwita et al, 2023 ), and ameliorating memory by restoring antioxidant mechanisms in the hippocampus. Through oxidation, vitamin C is hypothesized to shield cellular DNA, lipids, and proteins from oxidative damage caused by ROS and this can improve cognition ( Alqudah et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased oxidative stress is responsible for neuronal damage in the frontal cortex and hippocampus ( MacPherson et al, 2005 ), which is likely to impair learning. Vitamin C has an antioxidant potential that helps to oppose neurodegeneration in several ailments by conserving the antioxidant mechanism in the brain, imparting neuroprotection ( Dwita et al, 2023 ), and ameliorating memory by restoring antioxidant mechanisms in the hippocampus. Through oxidation, vitamin C is hypothesized to shield cellular DNA, lipids, and proteins from oxidative damage caused by ROS and this can improve cognition ( Alqudah et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to rutin (8 ppm) and catechin (5 ppm), researchers found that the aqueous extract of piper cubeba fruits also contained gallic acid (8 ppm), caffeic acid (13 ppm), syringic acid (3 ppm), and ferulic acid (11 ppm[21]. The aqueous extract from the same study contained 2.11 mg/g of total phenols [22].In some literature, oxygen atoms, and aromatic rings are considered the centers of adsorption in the four ingredients [22,23]. As a result, (P.cubebaOE) may be studied as an environmentally friendly corrosion inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some unanswered questions and possible applications for the future are highlighted. Dwita, Lusi & Iwo, M. &Mauludin, R. (2022) [4] Piper cubeba has a large diversity of lignans. These chemicals have antioxidant properties that could be useful in medicine, especially in the brain where they prevent neuronal damage.…”
mentioning
confidence: 99%